Advancing poliovirus eradication: lessons learned from piloting direct molecular detection of polioviruses in high-risk and priority geographies - Paula L. Marcet; Brandon Short; Ashley Deas; Hong Sun; Chelsea Harrington; Shahzad Shaukat; Muhammad Masroor Alam; Marycelin Baba; Adedayo Faneye; Prossy Namuwulya; Lea Necitas Apostol; Tamer Elshaarawy; et al. (Microbiology Spectrum)
ABSTRACT In the Global Polio Laboratory Network (GPLN), poliovirus (PV) screening results from acute flaccid paralysis (AFP) surveillance is based on virus isolation (VI) through cell culture, entailing long turnaround times and the amplification of live poliovirus. An alternative Direct Detection strategy (DD-ITD) for screening viral nucleic acid from stools, bypassing the need for virus culture, has been developed and extensively validated by GPLN partners. A multi-laboratory demonstration project was conceived to field-test the DD-ITD method by GPLN laboratories from the WHO African, Western Pacific, and Eastern Mediterranean regions, where wild serotype 1 or vaccine-derived polioviruses still circulate. Strategically selected laboratories were tasked to simultaneously process stool suspensions with the current gold-standard VI method and the new DD-ITD strategy. Results from 12 laboratories were compiled and analyzed to assess the quality of each RNA extraction and rRT-PCR run. Matched results for both methods of over 10,500 specimens showed an overall method agreement of 91%. All laboratories detected more PV presumptive positive samples with the DD-ITD strategy than with VI, but a large proportion of DD-ITD positive results (72%) were inconclusive or non-typeable, requiring confirmation through sequencing. A total of 298 (2.8%) samples were PV positive using both methods, 828 (7.9%) positive only for DD-ITD, and 62 (0.6%) positive only with VI. The DD-ITD overall performance, quality of results, and agreement between method results varied significantly across participating laboratories. DD-ITD implementation would entail building proficiency in advanced molecular laboratory techniques and data analysis, and increased demand for confirmatory sequencing.IMPORTANCESurveillance of acute flaccid paralysis (AFP) and sensitive poliovirus detection are key components of the WHO Global Polio Eradication Strategy. This work summarizes the results of a multi-laboratory evaluation designed to field-test the performance and applicability of a molecular Direct Detection strategy (DD-ITD) that does not require amplification of live poliovirus. AFP samples were processed in parallel with both the DD-ITD and the current gold-standard PV detection methodology, based on virus isolation (VI) through cell culture. All participating laboratories detected more PV presumptive positive samples using the DD-ITD strategy than with virus isolation methodology, although a higher proportion of DD-ITD results required confirmatory sequencing. Significant variability among laboratories was observed in the quality of the results and overall DD-ITD performance. Implementing DD-ITD would entail building proficiency in advanced molecular laboratory techniques and strengthening data analysis skills.